PERILAKU BULLYING TERHADAP PESERTA DIDIK KELAS VIII SMP MUHAMMADIYAH 1 PONTIANAK TAHUN 2018 - Kurniawan, Danni Candra; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractViolent acts of bullying experienced by children is the treatment that will impact the long term and would be a nightmare that never disappear from the memories of children who become victims. Based on information from teacher observation and BK, directly at the Junior High School Muhammadiyah 1 Pontianak that learners who seem doing the bullying. Therefore, researchers feel interested to conduct research on Junior High School Muhammadiyah 1 Pontianak because researchers want to find out more about bullying behavior in the students of Junior High School Muhammadiyah 1 Pontianak.The problem in this research is "How does the bullying behavior toward students of class VIII in Junior High School Muhammadiyah 1 Vampires?". This research aims to know the description of the behavior of bullying against the students of class VIII in Junior High School Muhammadiyah 1 Pontianak.The method used is descriptive method with survey research. The research sample is 30 students a class VIII Junior Muhammadiyah 1 Pontianak.This research uses a quantitative approach. This research data-collecting technique is the technique of indirect communication with a data-collecting lat; in the form of the now. Data analysis techniques using the calculation of the percentage.Based on the results of data analysis of bullying behaviours learners class VIII Junior High School Muhammadiyah 1 Pontianak overall reach 60.72% with "medium" category.Â Key Word: Bullying, Behaviour